Design of Wood-Based Gd (III)-Hemoporphyrin Monomethyl Ether Eco-Material for Optical Oxygen Sensing with a Wide Detection Range - Yujie Niu; Jinxin Wang; Zhongxing Zhang; Ting Liu (Sensors)
Gaseous oxygen detection is essential in numerous production and manufacturing sectors. To meet the varying oxygen detection requirements across different fields, techniques that offer a wide oxygen detection range should be developed. In this study, a wood-based oxygen sensing material was designed using balsa wood as the supporting matrix and gadolinium hemoporphyrin monomethyl ether (Gd-HMME) as the oxygen-sensitive indicator. The wood-based Gd-HMME exhibits a cellular porous structure, which not only facilitates the loading of a substantial number of indicator molecules but also enables the rapid interaction between indicators and oxygen molecules. OP is defined as the ratio of the phosphorescence intensity of the oxygen-sensing material in the anaerobic and aerobic environment. A linear relationship between OP and oxygen partial pressure ([O2]) was obtained within the whole range of [O2] (0–100 kPa). The wood-based Gd-HMME exhibited excellent resistance to photobleaching, along with a rapid response time (3.9 s) and recovery time (4.4 s). It was demonstrated that the measurement results obtained using wood-based Gd-HMME were not influenced by other gaseous components present in the air. An automatic oxygen detection system was developed using LabVIEW for practical use, and the limit of detection was determined to be 0.01 kPa.